Temporal Lobe Epilepsy in Multiple Sclerosis Resembling Autoimmune Limbic Encephalitis - FS, Ismail; CA, Lehrich; A, Dik; C, Strippel; A, Racz; S, Fuest; C, Muller; A, Johnen; S, Kovac; S, Knake; et al. (Archives of Clinical and Medical Case Reports, 2021)
Background: Temporal lobe seizures are typical symptoms in patients with Autoimmune Limbic Encephalitis (ALE), but also occur in the context of Multiple Sclerosis (MS). We here report a series of four patients with Temporal Lobe Epilepsy (TLE) and MS with features of ALE, focusing on clinical, MRI, EEG and serological findings. Case series: Four patients diagnosed with relapsingremitting (RR) or primary progressive (PP) forms of MS according to the amended McDonald criteria from 2017 and TLE with additional features of ALE (according the Graus criteria from 2016) were retrospectively identified based on medical records from five German tertiary epilepsy centers. All patients (female) suffered from additional limbic symptoms including memory disturbances and depression. All patients had additional signs of bilateral temporomesial affection on MRI and bilateral temporal slowing and epileptiform activity on EEG. Three patients had CSFspecific oligoclonal bands. In two patients TLE with additional limbic symptoms preceded MS, in one patient MS preceded TLE, and in one patient TLE and MS occurred simultaneously. In all cases, serum and CSF samples were negative for well-characterized neuronal antibodies. Conclusions: Our case series showed that TLE and MS symptoms may resemble the symptoms of ALE. Diagnosing of overlapping MS and ALE could not be made definitively because neither clinical symptoms nor temporomesial MRI findings could help clearly to distinguish between MS and antibody-negative ALE.